PENERAPAN TERAPI RENDAM KAKI DENGAN AIR HANGAT (HIDROTERAPI) UNTUK MENURUNKAN TEKANAN DARAH PADA IBU HAMIL TRIMESTER III DENGAN PREEKLAMPSIA RINGAN DI RUMAH SAKIT UMUM ASRI PURWAKARTA - Yuli Herlina; Grace Evelyn (Ensiklopedia Education Review, 2023)
Preeclampsia or Toxtemia gravidarum is high blood pressure accompanied byproteinuriawhosesymptomsusuallyappearat≥20weeksofgestation.Accordingto the World Health Organization, the prevalence of preeclampsia complicationsin developed countries is around 1.3%-6% and in developing countries around1.8%-18%. Based on data from the Directorate General of Public Health inIndonesia, there will be 1,077 cases of preeclampsia in 2022. West Java is aprovince with around 17.41% of preeclampsia. Based on research at one of theAsriPurwakartaGeneralHospitals,datawasfoundthattheincidenceofpreeclampsiain2022was269cases.Manytheoriesexplainthecausesofpreeclampsia, one of which is the older the gestational age, obesity and themother’s age. One way to treat mild preeclampsia is complementary therapy,namelysoakingyourfeetinwarmwater(hydrotherapy).Thisstudyfocusesontheapplication of warm water foot soak therapy (hydrotherapy) with the aim ofreducingbloodpressureinthirdtrimesterpregnantwomenwithmildpreeclampsia after 15 minutes of therapy for 3 consecutive days with a watertemperature of 37oC-48oC. The method used in this research is descriptiveresearch which is described to make a systematic and factual description. Thedesign used in research is a case study, namely a study to explore problems andapplications. The client was a pregnant woman in her third trimester with mildpreeclampsia who had an examination at the obgyn polyclinic at Asri GeneralHospital Purwakarta. The evaluation method of data analysis was carried outevery day after the application of the therapy. The results of the study found thatthe application of foot soak therapy with warm water (hydrotherapy) to reduceblood pressure in third trimester pregnant women with preeclampsia provedeffectivewithanaveragedecreaseinsystolicbloodpressureof19mmHgor13%and17 mmHg diastolicor20%.